Understanding the Historical Identities from the Position of Genealogy: Emphasis on Foucault’s Theory - Ali Ashraf Nazari; Afshin Ashkvar Kiyayi; Ahmad Saei; Kamaal Pooladi (رهیافتهای سیاسی و بین المللی)
Recognition of historical identities is done various narratives, including Primordialist, Postmodern and Historical Sociology, but we present to introduce the genealogy narrative of a historical identity with an emphasis on Foucault's theory. This narrative presumes always identity throughout history as a central issue in the context of the relationship of power. Accordingly, various forces in each historical period have tried to exercise power over historical identity, which did this through institutions, tools, techniques, tactics, and discourses. Also, as for "Contingency" of history, we have seen always the "fabrication" of various aspects of identity throughout history. The main issue of the present paper is the recognition of Foucault's genealogy method and differences between Foucault's methods and other available methods. Based on this, we distinguish differences of Foucault's methodology with other methods of identity, and then we investigate the characteristics of the Foucaultian method about identity.